THE DISCOURSE OF ISLAMIC BOARDING SCHOOL RESISTANCE SYSTEM ON THE THEOLOGY IN THE SCHOOL IN â€œPUISI UNTUK ADIKâ€ BY WIJI THUKUL - Alfian Setya Nugraha; Andrik Purwasito; Haris Supratno; Titis Srimuda Pitana (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2019)
AbstractThe Islamic boarding school is a place to get the theology. It such an educational place needed to developing an educational system to supply the students to in order to following the development era. Moreover today the Islamic boarding schoollook at that religious learning in the public schools are very lacking, the next generation of young people only get about two hours of religious subject. It has cause to the emergence of resistance in the Islamic boarding school society to open a public school but also it combined with the religion. This article applies thediscourse theory, semiotic, and resistance in the theologyin Indonesia, especially in the Islamic boarding school area. This research methodused the qualitative method to describe the resistance discourse phenomena in the theology in the Islamic Boarding school.Keywords: Discourse, Resistance, Islamic boarding school